INVESTIGATION OF THE TREND BETWEEN THE RESULTS OF THE BARKHAUSEN MAGNETIC NOISE (MBN) METHOD WITH CLASSICAL METHODS FOR ION NITRIDED TESTING OF STEEL, BH11 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The Barkhausen magnetic noise (MBN) method has emerged as a promising technique for non-destructive measurement of residual stresses, especially in ion nitrided instrumental steels. The study determines the applicability of MBN in comparison to traditional X-ray diffraction (XRD), relative wear resistance and microhardness measurements by focusing on its potential for faster and more reliable evaluations. The comparison is made on MBN speed because it provides a rapid assessment compared to other methods that often require more extensive sample preparation and longer measurement times. MBN does not alter the test material, preserving its integrity for later use. While traditional methods, such as XRD, are surface sensitive, MBN can offer information on subsurface stresses depending on the measurement configuration. The correlation performed, links the study on the one hand to the process logic and on the other hand to microhardness and tribological testing.